A Bandwidth Efficiency Optimized Frequency Domain Equalization Concept for Single Carrier Transmission - Witschnig, Harald; Stallinger, H.; Huemer, Mario (Lecture Notes in Computer Science, 2007)
The concept of Single Carrier Transmission with Frequency Domain Equalization (SC/FDE) represents one of the most powerful strategies for next generation wireless communication systems. One of the main advantages of this concept, which makes use of a so called cyclic prefix (CP), is its powerful and low complexity equalization procedure in frequency domain. In this paper we investigate frequency domain equalization schemes based on the more bandwidth efficient concepts of Overlap and Add (OA) and Overlap and Save (OS). We explore the main problem of these approaches, namely the difficult predefinition of a maximum equalizer length, and we present a solution which results in a bit error performance absolutely comparable to the CP based equalizer.
elib2cris::1512001600,witschnig2007